Analisis Dampak Kepemimpinan Transformasional terhadap Kepuasan Kerja dan Retensi Karyawan di Kecamatan Sedati Sidoarjo - Rifki Suwaji; Rina Indra Sabella; Erwin Tjahjuadi; Waloyo, Waloyo; Agus Iwhan Ariftian Zuhdi (MAMEN: Jurnal Manajemen, 2025)
This study aims to analyze the impact of transformational leadership on job satisfaction and employee retention in Sedati Subdistrict, Sidoarjo Regency. A descriptive qualitative approach was employed, utilizing in-depth interviews and participant observations for data collection. The research informants included employees and leaders from various local organizations, including MSMEs and service institutions. Thematic analysis was used to identify patterns of meaning in the interactions between leaders and employees.The findings reveal that transformational leadership practices in Sedati foster a positive work environment, enhance employee motivation, and strengthen employee loyalty. Dimensions such as visionary inspiration, personalized attention, and open communication emerged as key factors in increasing job satisfaction. Furthermore, strong interpersonal relationships between leaders and employees directly influenced employee retention, as employees felt valued and emotionally connected to their organizations. This research also highlights the significance of individualized consideration and moral support from leaders as the foundation for cultivating a healthy and inclusive organizational culture. The practical implications of these findings underscore the need for leadership training focused on human-centered relationship development. This study contributes to the enrichment of local leadership literature and provides a basis for organizational decision-making aimed at improving job satisfaction and retaining employees.